2015
DOI: 10.2147/vmrr.s72373
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the MDR1 mutant allele associated with multidrug sensitivity in dogs from Brazil

Abstract: To date, a 4-bp deletion in the MDR1 gene has been detected in more than ten dog breeds, as well as in mixed breed dogs, in several countries, however information regarding this mutation in dogs from Brazil is lacking. For this reason, 103 Collies, 77 Border Collies, 76 Shetland Sheepdogs, 20 Old English Sheepdogs, 55 German Shepherds, 16 Australian Shepherds, and 53 Whippets from Brazil were screened for the presence of the mutation. The heterozygous mutated genotype, MDR1 (+/−), frequency found for Collies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 21 publications
5
17
0
6
Order By: Relevance
“…11 Slightly lower results in MDR1 mutant frequency have been recorded in Germany: 59 per cent, 7 55 per cent, 12 in Japan 58.3 per cent, 13 Australia 56 per cent 14 and Brazil 61.2 per cent. 3 In AuS, the MDR1 mutated allele frequency in Italy was calculated to be 35 per cent, a mean value considering it ranged from 15.7 per cent in Brazil 2 to 46 per cent in UK. 4 In the USA, the country of origin of AuS breed, Neff et al 1 and Mealey and Meurs 10 reported a mutant allele frequency of 17 per cent and 29 per cent, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…11 Slightly lower results in MDR1 mutant frequency have been recorded in Germany: 59 per cent, 7 55 per cent, 12 in Japan 58.3 per cent, 13 Australia 56 per cent 14 and Brazil 61.2 per cent. 3 In AuS, the MDR1 mutated allele frequency in Italy was calculated to be 35 per cent, a mean value considering it ranged from 15.7 per cent in Brazil 2 to 46 per cent in UK. 4 In the USA, the country of origin of AuS breed, Neff et al 1 and Mealey and Meurs 10 reported a mutant allele frequency of 17 per cent and 29 per cent, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…About Whi: the mutation has been described in the FCI as unrecognised long-haired whippet SiW in the USA with a 16-18 per cent frequency, 1 10 but no mutation was found in the 14 samples analysed in UK by Tappin et al in 2012 4 and in the 53 samples tested by Monobe and colleagues in Brazil. 3 MDR1 mutation test is available since 2008 when the first animals were tested for (2009 n=0, 2010 n=2, 2011 n=3). A clear increase in the number of animals tested has been recorded since 2012 (n=44).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…al. 2010;Mizukami et al 2012;Mizukami et al 2013;Monobe et al 2015), yet the most important mutation remains the one which leads to a loss of four base pairs in 227-230 nucleotide, known as MDR1 (c.227-230del) or ABCB1-1Δ (Mizukami et al 2012).…”
Section: Introductionmentioning
confidence: 99%